Impact of physico-chemical properties on falling liquid films flow over flat and corrugated surfaces. (October 2022) - Sayegh, Mohamad AL; Rouzineau, David; Meyer, Michel; Cid, Emmanuel; Alix, Pascal; Dalmazzone, Christine; Roesler, John
Highlights: Fluorescence intensity and optical flow methods are used to analyze liquid film thickness and interfacial velocity. Decreasing surface tension has a stabilizing effect on the flow. At high viscosity, solitary waves with high thickness followed by a thin free-wave film appear. Capillary waves are attenuated, solitary waves thickness is increased and velocity is reduced by the counter-current gas. The breaking-waves phenomenon was observed on corrugated geometry, especially for low surface tension fluids. Abstract: In this paper, an optical technique based on fluorescence intensity is applied and calibrated to simultaneously measure film thickness (up to 8 mm) and interfacial velocity of the liquid film flow. Thus, thin-film flows at intermediate and low Reynolds number (13 <  Re  < 290) are experimentally studied with special attention given to the spatial variation, the frequency of the waves, and interfacial liquid velocity associated with global visual observation. Two fluids (water-ethanol mixture) characterized by low surface tension ( σ  = 35 and 50 mN/m) and three fluids (water-glycerin mixture) with high viscosity ( µ  = 5, 10, and 15 mPa.s) are used to investigate the influence of physico-chemical properties on thin-film flow on flat and corrugated plate topologies. First, the effect of physico-chemical properties on the global variation of waves shape and instability evolution has been investigated. Different work fluids were used in the same experimental conditions on a flat plate. Results showed that decreasing surface tension has a stabilizing effect on the flow, dampening the capillary waves that should otherwise arise. At high viscosity, solitary waves with high thickness followed by an undisturbed thin-film with a constant thickness appear. The impact of liquid flow rate and inclination ( θ  = 10° and 20°) was also studied. It shows that at higher inclination the film thickness decreases and then increases as the liquid flow rate increases. Next, the impact of counter-current gas was studied and we demonstrated that the amplitude of the main waves significantly increases even at low gas velocity while the effect on the velocity of the wave starts to be significant at a counter-current gas velocity of 3 – 4 m/s. Finally, the effect of the corrugation of the solid plate at a high inclination angle ( θ  = 60°) shows the onset of the breaking waves phenomenon, especially for fluids with low surface tension.